COST REDUCTION STRATEGIES THROUGH EFFICIENT ROVING WASTE RECYCLING IN SPINNING MILLS (International conference on multidisciplinary science, 2026)
The increasing cost of raw cotton and growing environmental concerns have intensified the need for efficient waste management strategies in the textile industry. Roving waste generated during the roving and spinning processes represents a significant source of material loss in spinning mills. This study investigates cost reduction strategies achieved through efficient recycling of roving waste using improved mechanical processing methods. The research focuses on machine optimization, process parameter control, and blending strategies to enhance fiber recovery and reduce production costs. Experimental and analytical evaluations indicate that the effective recycling of roving waste can substantially decrease raw material consumption while maintaining acceptable yarn quality. The results demonstrate that roving waste recycling is not only economically beneficial but also supports sustainable and circular textile production.